Architectural characteristics of Malay traditional houses through decorative elements: A comparison between Perak Limas' House (PLH) andJohor Limas' House (JLH) / Sabrizaa Rashid, Nurfaisal Baharuddin and Kartina Alauddin - Rashid, Sabrizaa; Baharuddin, Nurfaisal; Alauddin, Kartina (Universiti Teknologi MARA, Perak, 2021)
Malay Traditional houses were classified based on roof design, spatial organization, construction method, geographical setting and decorative elements particularly at every state in Malaysia. This article analyzes decorative elements on the traditional Malay houses in two states; Perak Limas' House (PLH) in Perak and Johor Limas' House (JLH) in Johor. The research aim is to establish the architectural characteristics of both PLH and JLH. This can be achieved by identifying the existence of decorative elements and carrying out a comparative study on both PLH and JLH on the decorative elements as the main architectural characteristic. Twenty-five of PLH and JLH were selected for the study. The study found similarities and dissimilarities that contribute to the extension of aesthetical theory of the Malay traditional house in Malaysia. The findings established the architectural attributes of traditional houses in Perak and Johor through decorative elements.